High-resolution spectral imaging of SNR W44 and IC443 at 22 GHz with the Sardinia Radio Telescope. Issue Volume 12:Issue S331(2017) (17th October 2017) - Loru, S.; Pellizzoni, A.; Egron, E.; Iacolina, N.; Righini, S.; Marongiu, M.; Mulas, S.; Murtas, G.; Simeone, D.; Pilia, M.; Bachetti, M.; Trois, A.; et al.
Abstract: In the framework of the Astronomical Validation and Early Science activities of the Sardinia Radio Telescope (SRT, www.srt.inaf.it ), we performed 22 GHz imaging observations of SNR W44 and IC443. Thanks to the single-dish imaging performances of SRT and innovative ad hoc imaging techniques, we obtained maps that provide a detailed view of the structure of the remnants. We are planning to exploit the high-frequency radio data of SNRs to better characterize the spatially-resolved spectra and search for possible spectral steepening or breaks in selected SNR regions, assessing the high-energy tail of the region-dependent electron distribution.